Analysis of students’ critical thinking ability in solving open-ended problems in arithmetic sequences - Ani Noraini; Anggita Oktaviana Putri (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
Critical thinking is an advanced thinking skill that requires students to think rationally and logically. This study aims to describe the critical thinking ability of students. The research was conducted in MAN 1 Malang in class XB, consisting of 32 students. The method used was descriptive qualitative research with three subjects representing high, medium, and low categories of critical thinking skills. The data collection techniques used were tests and interviews. The data analysis technique used was the analysis of test scores and interviews, with a credibility test for data validity. The results showed that high-category subjects were able to fulfill six critical thinking indicators (interpretation, analysis, evaluation, conclusion, explanation, and self-regulation) and could answer in two different ways. Medium-category subjects were able to fulfill the indicators of interpretation, analysis, conclusion, explanation, and self-regulation, although there were less precise answers. Subjects in the low-category did not meet the indicators of critical thinking skills and could only answer in one inappropriate way. Based on these results, teachers can provide open-ended or non-routine problem sets to improve students' critical thinking skills.